2013
DOI: 10.1002/erv.2239
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Anorexia Nervosa Have Their Say: A Review of Qualitative Studies on Treatment and Recovery from Anorexia Nervosa

Abstract: Anorexia nervosa often begins in adolescence, and there is a growing body of quantitative literature looking at the efficacy of treatment for adolescents. However, qualitative research has a valuable contribution to make to the understanding of treatment and recovery. This paper aims to review qualitative studies on the experience of treatment and recovery for adolescents with anorexia nervosa. Key themes from the 11 studies identified the role of family, peers and professionals, family therapy, the inpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 59 publications
2
80
0
10
Order By: Relevance
“…They selected and analyzed 16 studies and described original concepts of recovery, especially self-acceptance and self-reconciliation. Bezance and Holliday [20], who selected and analyzed 11 articles, investigated the perspective of adolescents with AN. They underlined the importance of family involvement in care, of peer groups, and of the need for a comprehensive bio-psycho-social approach.…”
Section: Introductionmentioning
confidence: 99%
“…They selected and analyzed 16 studies and described original concepts of recovery, especially self-acceptance and self-reconciliation. Bezance and Holliday [20], who selected and analyzed 11 articles, investigated the perspective of adolescents with AN. They underlined the importance of family involvement in care, of peer groups, and of the need for a comprehensive bio-psycho-social approach.…”
Section: Introductionmentioning
confidence: 99%
“…With engagement of characteristically ambivalent patients [15] critical to treatment success, and engagement dependent on acceptability of treatment, a thorough qualitative understanding of inpatient care from the patients' perspective is needed to optimise outcomes [29,30]. Aiming to contribute to the growing evidence base and inform service improvement locally we set out to describe the experiences of adults admitted to hospital for treatment of eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that individuals with AN will disengage from treatment and turn to eating disorder behaviors during periods of enforced treatment (e.g., nasogastric tube feeding) or power struggles. 26-27 As patients repeatedly struggle to abate their fears and regain a sense of control, patterns of behaviors to prevent weight gain may become even more deep-rooted.…”
Section: The Roy Adaptation Modelmentioning
confidence: 99%